2015
DOI: 10.1007/s13300-015-0112-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Liraglutide in a Real-World Setting in Spain: eDiabetes-Monitor SEEN Diabetes Mellitus Working Group Study

Abstract: IntroductionA limitation with randomized controlled trials is that, while they provide unbiased evidence of the efficacy of interventions, they do so under unreal conditions and in a very limited and highly selected patient population. Our aim was to provide data about the effectiveness of liraglutide treatment in a real-world and clinical practice setting.MethodsIn a retrospective and observational study, data from 753 patients with type 2 diabetes were recorded through an online tool (eDiabetes-Monitor).Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
19
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 22 publications
18
19
2
Order By: Relevance
“…In total, 63.4% and 76.7% of PCP- and specialist-treated patients, respectively, had an initial BMI ≥30 kg/m 2 , and reductions in body weight and BMI after 2 years’ follow-up were statistically significant for both cohorts and consistent with those reported in RCTs [39] and other studies assessing the effectiveness of liraglutide [24, 25]. …”
Section: Discussionsupporting
confidence: 81%
“…In total, 63.4% and 76.7% of PCP- and specialist-treated patients, respectively, had an initial BMI ≥30 kg/m 2 , and reductions in body weight and BMI after 2 years’ follow-up were statistically significant for both cohorts and consistent with those reported in RCTs [39] and other studies assessing the effectiveness of liraglutide [24, 25]. …”
Section: Discussionsupporting
confidence: 81%
“…In addition, the clinical effectiveness and cost-effectiveness of both liraglutide 1.2 mg and liraglutide 1.8 mg, compared with sitagliptin, have been demonstrated in Spain [1820]. The present analysis suggests that liraglutide 1.8 mg was also cost-effective compared with lixisenatide 20 μg in the Spanish setting.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, the ability of liraglutide to reduce HbA1c and weight was demonstrated in real-world clinical practice in Spain [20]. However, no studies comparing the cost-effectiveness of liraglutide versus lixisenatide in the Spanish setting have been published to date.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the studies assessed the clinical effectiveness of liraglutide without an active comparator (81.4%; N  = 35) [28, 29, 31, 34, 3639, 41–49, 5155, 57, 6064, 66–71]. Real-world studies with comparators were less frequently observed (18.6%; N  = 8); the most common comparators for liraglutide were: sitagliptin or any DPP-4i ( N  = 6) [32, 33, 35, 40, 56, 58], exenatide ( N  = 3) [33, 35, 50], glimepiride or any other SUs ( N  = 2) [30, 35], pioglitazone or other TZDs ( N  = 1) [35], and MET ( N  = 1) [35]; note: these numbers do not add up because some studies had more than one comparator.…”
Section: Resultsmentioning
confidence: 99%